Correlation between coagulation and inflammation state in patients with diabetes mellitus type 2 in relation to gender differences: is there any impact of eight-week exercise training? - Trebinjac, Divna; Petronic, Ivana; Lalic, Nebojsa; Nikolic, Dejan (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. The hypercoagulable state and inflammation state in diabetics has been widely studied by previous researchers, but there is a lack of research about a possible impact of exercise training on this relationship. The aim of this study was to assess and compare correlation between the coagulation and inflammation status in patients with type 2 diabetes mellitus taking into account the gender differences as well as an impact of the 8-week exercise training on the correlation coefficient and parameters of the inflammation and coagulation state. Methods. A total of 60 patients in stable clinical condition and well-regulated diabetic status passed through all phases of the study. The exercise training included the exercise program as interval training with estimated intensity uphill to 75% of a maximal heart rate in particular individual, 5 times a week for 8 weeks, and walking for 30 minutes with a speed of 5 km/h, 5 times a week for 8 weeks. Further fibrinolytic, coagulation and inflammatory parameters were analyzed before and after the study: D-dimer, von Willebrand factor (vWF), fibrinogen, high sensitivity CRP (hs-CRP), leukocytes, thrombin time (TT), prothrombin time (PT), activated partial thromboplastin time (APTT) and coagulation factors: FII, FV, FVII and FX. Results. Our research showed a statistically significant reduction in the mean vWF levels after intervention both at the males (p < 0.001) and females (p < 0.001). According to a correlation analysis between hs-CRP and fibrinogen, there was a positive correlation as baseline both at the males (p < 0.05, r = 0.492) and females (p < 0.01, r = 0.516) which became weaker in the males (p < 0.01, r = 0.449) and disappeared in the females (p < 0.05, r = 0.059) after intervention. The correlation which existed as baseline in the males between D-dimer and either hs-CRP (p < 0.01, r = 0.633) or fibrinogen (p < 0.01, r = 0.673) as well as the correlation between hs-CRP and FII (p < 0.01, r = 0.728), FV (p < 0.05, r = 0.366), FVII (p < 0.05, r = 0.373) coagulation as well as between D-dimer and FII (p < 0.01, r = 0.851), FVII (p < 0.05, r = 0.367)was absent in the females. Our research demonstrated a weakening correlations in the males after intervention between D-dimer and hs-CRP (p < 0.05, r = 0.378), between hs-CRP and FII (p < 0.01, r = 0.501), FV (p < 0.05, r = 0.298), FVII (p < 0.05, r = 0.351) as well as between D-dimer and FII (p < 0.01, r = 0.759), and FVII (p < 0.05, r = 0.296). The increase of the FX values (p < 0.05) in the females after intervention suggested the possible antiinflammatory effect of exercise training. Conclusion. According to previous research, the higher levels of vWF was associated with a risk of cardiovascular disease in people with type 2 diabetes mellitus and vWF may be a risk factor unique to these populations. We demonstrated that the 8-week exercise training can significantly reduce the value of vWF in the males and females, suggesting a potential beneficial effect on the endothelial function parameters. Our research demonstrated a stronger correlation between the coagulation and inflammation parameters as baseline in the males than in the females with type 2 diabetes mellitus. According to our results, the 8-week exercise training lead to a weakening of the strength of correlation between the coagulation and inflammation parameters in the males and complete disappearance of this correlation in the females, suggesting a unique effect of exercise training that should be explored in future research.